(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Setia Abadi is a company engaged in the field of trade in goods and services in the category of printing. The method use in the final report is descriptive method and how to obtain these data with field studies and literature. Based on the results of practical work it can be concluded that recording, valuation, presentation, and disclosure of inventory has been done according to the Financial Accounting Standards Board and controlling of inventory in the warehouse is adequate. Recording method performed by this company is a physical method to the valuation method FIFO (First In, First Out) where two things are in accordance with the Financial Accounting Standards. Income Statement presented in accordance accounting principles that are based on the entities without public accountability.